Activation of the anti-cancer agent upamostat by the mARC enzyme system. (4th February 2013) - Froriep, Danilo; Clement, Bernd; Bittner, Florian; Mendel, Ralf R.; Reichmann, Debora; Schmalix, Wolfgang; Havemeyer, Antje
Abstract: 1. Upamostat (Mesupron®) is a new small molecule serine protease inhibitor. The drug candidate was developed to inhibit the urokinase-type plasminogen activator (uPA) system, which plays a major role in tumor invasion and metastasis. Upamostat is currently in clinical development as an anti-metastatic and non-cytotoxic agent against pancreatic and breast cancer. 2. Upamostat is the orally available amidoxime- (i.e. hydroxyamidine-) prodrug of the pharmacologically active form, WX-UK1. In this study, the reductive enzymatic activation of upamostat to its corresponding amidine WX-UK1 was analyzed. 3. The recently discovered molybdenum enzyme "mitochondrial Amidoxime Reducing Component" (mARC) catalyses together with its electron transport proteins cytochrome b5 and NADH cytochrome b5 reductase the reduction of N -hydroxylated prodrugs. In vitro biotransformation assays with porcine subcellular fractions and the reconstituted human enzymes demonstrate an mARC-dependent N -reduction of upamostat.